Immigration Travel Documents Section Performance Analysis Tanjung Perak in State Administration - Oky Sabastian; Fedianty Augustinah; Eny Hartati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study provides a comprehensive analysis of the performance of the Travel Document Section at Tanjung Perak Immigration Office within the framework of Public Administration. Employing a qualitative, case-study approach, the research investigates the efficiency, effectiveness, and quality of immigration services, emphasising the application of New Public Management (NPM) principles and Good Governance practices. The findings reveal that while technological innovations such as digital systems (M-Passport and SIMKIM) have successfully improved operational efficiency and reduced physical queues, challenges persist regarding procedural transparency, accountability, and system reliability. Human errors and inconsistent discretion in handling complex documents highlight the need for enhanced capacity building and resource allocation. Moreover, issues of bureaucratic transparency and integrity undermine public trust, underscoring the importance of strengthening internal controls and communication strategies. The study also underscores that service quality is multidimensional, encompassing physical facilities, interpersonal professionalism, and procedural clarity, all of which influence public satisfaction. Despite improvements, the gap between technological efficiency and service effectiveness suggests that further efforts are needed to integrate digital innovations with robust procedural protocols. The research concludes that sustainable performance improvement requires a balanced focus on technological, human, and systemic factors, fostering a culture of transparency, accountability, and continuous development. These insights offer valuable policy recommendations to enhance the robustness and responsiveness of immigration services, ultimately strengthening the legitimacy and trust of government institutions in delivering public services.